An ancient influenza genome from Switzerland allows deeper insights into host adaptation during the 1918 flu pandemic in Europe - Christian Urban; Bram Vrancken; Livia V. Patrono; Ariane Düx; Mathilde Le Vu; Katarina L. Matthes; Nina Maria Burkhard-Koren; Navena Widulin; Thomas Schnalke; Sabina Carraro; Frank Rühli; Philippe Lemey; et al. (BMC Biology)
Abstract Background From 1918 to 1920, the largest influenza A virus (IAV) pandemic known to date spread globally causing between 20 to 100 million deaths. Historical records have captured critical aspects of the disease dynamics, such as the occurrence and severity of the pandemic waves. Yet, other important pieces of information such as the mutations that allowed the virus to adapt to its new host can only be obtained from IAV genomes. The analysis of specimens collected during the pandemic and still preserved in historical pathology collections can significantly contribute to a better understanding of its course. However, efficient RNA processing protocols are required to work with such specimens. Results Here, we describe an alternative protocol for efficient ancient RNA sequencing and evaluate its performance on historical samples, including a published positive control. The phenol/chloroform-free protocol efficiently recovers ancient viral RNA, especially small fragments, and maintains information about RNA fragment directionality through incorporating fragments by a ligation-based approach. One of the assessed historical samples allowed for the recovery of the first 1918 IAV genome from Switzerland. This genome, derived from a patient deceased during the beginning of the first pandemic wave in Switzerland, already harbours mutations linked to human adaptation. Conclusion We introduce an alternative, efficient workflow for ancient RNA recovery from formalin-fixed wet specimens. We also present the first precisely dated and complete influenza genome from Europe, highlighting the early occurrence of mutations associated with adaptation to humans during the first European wave of the 1918 pandemic.